Stereotip Perempuan dan Budaya Patriarkal Berlatar Islam dalam Novel Religi Best Seller Tahun 2000-2021 - Lukman Hakim; Hasrul Rahman; Robby Yudhi Nurhana (Muslim Heritage, 2023)
AbstractThis research is a study of the image or stereotype of women in literary works, especially spiritual novels. This research interesting because many religious values in religious novels are considered counterfeminist and place women under male domination. The purpose of this research is to reveal stereotypes of women and patriarchal culture in the best selling spiritual novels for 2000-2021. This research was conducted by means of text or discourse analysis which investigates an event, either in the form of an act or writing in the best seller Spiritual Novels of 2000-2021 which is examined to obtain the exact facts (find the origins, causes, true causes, and so on). . The results of this study, namely: First. Women in the novel under study are still seen as people from the second class. There are many scenes showing women being discriminated against. Second, patriarchal culture still dominates stories in novels, especially religious novels. Many quotes show hegemony over women. Third, the socio-cultural background of the author influences the style of the novel's story. The setting of the novel is always related to the real life of the author. AbstrakPenelitian ini merupakan kajian terhadap citra atau stereotip perempuan dan budaya patriarkal berlatar islam dalam karya sastra khususnya novel Religi. Penelitian ini menjadi menarik karena nilai agama dalam novel religi banyak yang dianggap kontrafeminis dan menempatkan perempuan dalam dominasi laki laki.  Tujuan penelitian ini adalah untuk menyingkap stereotip perempuan dan budaya patriarki dalam novel Religi best seller tahun 2000-2021. Penelitian ini dilakukan dengan analisis teks atau wacana yang menyelidiki suatu peristiwa, baik berupa perbuatan atau tulisan dalam Novel Religi best seller tahun 2000-2021 yang diteliti untuk mendapatkan fakta-fakta yang tepat (menemukan asal-usul, sebab, penyebab sebenarnya, dan sebagainya). Hasil penelitian ini, yaitu: Pertama. Perempuan dalam novel yang diteliti  masih dipandang sebagai orang dari golongan kedua. Banyak adegan yang memperlihatkan perempuan mendapatkan diskriminasi. Kedua, budaya patriarki masih mendominasi cerita dalam novel khususnya novel religi. Banyak kutipan yang memperlihatkan hegemoni terhadap perempuan. Ketiga, latar sosial budaya pengarang berpengaruh terhadap corak cerita novel. Latar novel selalu berkaitan dengan kehidupan pengarang yang sebenarnya.